The usefulness of [99mTc]MIBI scintigraphy in the diagnostic algorithm of ultrasonographical suspected thyroid nodules by using EU-TIRADS criteria - Manevska, Nevena; Makazlieva, Tanja; Stoilovska Rizova, Bojana; Stojanoski, Sinisa (Nuclear medicine review. Central & Eastern Europe, 2023)
Although not yet involved in the algorithm of thyroid nodules, 99mTc-methoxy-isobutyl-isonitrile ([99mTc]MIBI) scintigraphy may help in the individual diagnostic workup of a thyroid patient, especially where indeterminate fine needle aspiration biopsy (FNAB) is present. The aim of this study was to evaluate the usefulness of [99mTc]MIBI thyroid scintigraphy in the diagnostic algorithm of thyroid nodules, particularly in ultrasound EU-TIRADS 4 or 5 lesions, that cytologically were either indeterminate or benign. ETHODS: A retrospective randomized study, including 42 thyroid patients, with mean age 47 ± 17 years, was conducted. [99mTc]MIBI scan was compared with ultrasound (US) EU-TIRADS criteria, pertechnetate scan, FNAB and histopathological findings for the differentiation of malignant thyroid nodules from benign lesions. The US mainly detected hypoechoic inhomogeneous presentation of the thyroid nodules (35/42, 83.33%), 4 cases with isoechoic nodules and 2 cases presented with hyperechoic thyroid nodules. Histopathology revealed malignancy in 15/42 (35.71%), while all other patients 27/42 (64.29%) were benign. Visual analysis score showed that patients scored with 1+ and 2+ were statistically significant to be benign, while 13 vs. 10 pts that were visual score 3+ were malignant vs. benign (p > 0.05). Sensitivity was 100%, while specificity was very low 22.22%, PPV was 41.67%. Even [99mTc]MIBI scan is not routinely used as a daily practice diagnostic tool of thyroid nodules, we will further apply it on a larger group of patients and try to quantify the uptake of the radiotracer to see whether it will help in the diagnostic algorithm of thyroid nodules.